A influência da pirataria sobre a popularização de animações japonesas entre os jovens - Moura, Giovanna Gabrielle Albuquerque de (2022)
In the following undergraduate thesis, the relationship between the consumption of Japanese animations linked to the distribution of works without copyright (piracy) will be addressed. In order to do so, it will be discussed about the history and origin of fansubs and also the history and genres of anime will be explored. Added to a research with young audience in Brazil from 15 to 30 years old. Therefore, the main objective of the work is to track data about the consummation of piracy among this specific group, also creating a reflection on the ethical issues of this practice in the context of the media society in which we are inserted.